Serum levels of environmental pollutants is a risk factor for breast cancer in Inuit: a case control study - Maria Wielsøe; Peder Kern; Eva Cecilie Bonefeld-Jørgensen (BMC, 2017)
Abstract Background Environmental Persistent Organic Pollutants (POPs) can alter the hormone homeostasis by mimicking, interfering or blocking the function of hormones; moreover POPs are hypothesized to modify the risk of breast cancer. The association between POPs and breast cancer has been widely studied but the conclusions are inconsistent. The present study examined the associations between serum levels of POPs and breast cancer with focus on the highly exposed Greenlandic Inuit population. Methods The study design was a case-control study of Inuit women from Greenland. The participants were asked to complete a questionnaire with information on reproductive history and lifestyle and to provide a blood sample. The sampling was carried out in two time periods (2000-2003 and 2011-2014). The serum levels were determined of 14 polychlorinated biphenyls (PCBs), 11 organochlorine pesticides (OCPs), 16 perfluoroalkyl acids (PFAAs), 1 polybrominated biphenyl (PBB), and 9 polybrominated diphenyl ethers (PBDEs). Independent samples t-test was used to compare differences between cases and controls and odds ratios (OR) adjusted for identified confounders were obtained using logistic regression. Results The study population included 77 breast cancer cases and 84 controls. The majority of the measured compounds declined significantly from 2000 - 2003 to 2011-2014. However, for the perfluorinated carboxylic acids (PFCAs) an increase was observed. The serum levels were significantly higher in cases compared to controls for the majority of the compounds, and after adjusting for age the difference was maintained for ∑OCP, dichlorodiphenyldichloroethylene (p,p'-DDE), ∑PFAA, ∑perfluorinated sulfonic acids (PFSA), perfluorohexane sulfonate (PFHxS), and perfluorooctane sulfonate (PFOS). For the lipophilic POPs, high serum levels (middel/highest vs. lowest tertile) of ∑PCB, ∑estrgoenicPCB, PCB99, PCB138, PCB153, PCB170, PCB170, and PCB183 was associated with breast cancer risk; for the amphiphilic PFAAs, high serum levels of ∑PFAA, ∑PFCA, ∑PFSA, perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), PFHxS, and PFOS were associated with breast cancer risk. Conclusion Significant, positive associations between breast cancer risk and PCBs and PFAAs were observed. The associations indicate that environmental exposure to POPs can be a factor increasing the risk for breast cancer in Inuit women.